Faktor-Faktor Yang Mempengaruhi Pendapatan Nelayan Di Pasar Bawah Kota Manna - Sakuan Sakuan (Fakultas Ekonomi Universitas Prof. Dr. Hazairin, SH. Bengkulu, 2018)
The research was conducted in Manna Urban Village Urban Village, research area: Capital, Fish Catch (Production), Working Hour and Fisherman's Revenue. The purpose of research to determine the effect of Capital, Fish Catch (Production), Working Hours to Fisherman's Revenue Type research research research. Total sample 48 people. The sampling technique is done by Random sampling. Data analysis tools use Multiple Linear Regression and Correlation. Partial test of hypothesis using test tool of t Test Statistic and test simultaneously using F-test test, Capital Effect equal to 1,198, influence of fish catch (Production) equal to 0,940, influence of working hours equal to 0,196 Correlation coefficient (R) = 0,984. Coefficient of Determination ((RÂ²)) = 0.966.Partial test obtained by value of t1-count bigger. 14,012. This means that Capital significantly affects the income of fishermen. Value t2-counted 15.955, meaning that the production or the catch of fish also have a significant effect on fisherman's income, as well as the value of t3 count. 2,165, this means working hours also have a significant effect on fisherman's income. Then Test simultaneously the F-count value is greater than the F-table value (445,540> 4.68). This means that simultaneously the Capital, Fish Catch (Production) and Working Hour significantly influence Fisherman's Income in Manna City Urban Village.